(untitled) (Journal of Geography and Environmental Management, 2018)
Among the various forms and direction of cooperation between states, an interstate innovative interaction that unites information resources, which gives a systematic character to innovative development and promotes the commercialization of innovative ideas, was objectively necessary. In the border areas, the influence of interstate and national programs on environmental and environmental, cultural and socio-ecological interaction is being expanded. But an important role is given to information support of international scientific, technical and innovative cooperation of research and production companies, small and medium-sized enterprises, production teams, development of scientific and innovation potential. A common characteristic of modern territorial activity is the information of economic entities and the information registration of socio-natural processes. The exchange of information and other types of information activity of border economic entities is the basis for successful economic and environmental international cooperation. The process of informatization of the border areas of neighboring countries is characterized by technological and organizational features, but is generally determined by the introduction of common technical innovations: the use of microprocessing technology; digital data storage; use of the Internet; The application of geoinformation technology and global positioning tools.